Pemanfaatan Data Transaksi Untuk Mewujudkan Kepuasan Pelanggan, Brand Awareness Dan Loyalitas Pelanggan - Noviadry Nur Tamtama; Erma Widyastuti; Rahmawati Riantisari (ANALOGI Jurnal Ilmu Sosial dan Humaniora, 2024)
Business development and growth is the ultimate target of establishing a company. Apart from being sales data, transaction data can also be a company asset that can be used for operational management and marketing strategies. For operational purposes, transaction data that reflects customer capabilities and conditions can be used for inventory management purposes by predicting the need for raw materials to guarantee the availability of products or services within a certain period of time according to customer needs. Companies can also develop products according to customer needs and minimize unnecessary expenses resulting from excessive procurement of raw materials. For marketing purposes, transaction data can be a reference for determining demographic customer characteristics. Customer characteristics can be used as a tool to determine current customer segments and how to provide maximum service to customers. The overall condition of customers will be valuable information for companies in carrying out marketing strategies. This research will explain how to utilize sales transaction data during a certain period using qualitative methods to achieve customer satisfaction through good raw material inventory management and appropriate product and service development, creating brand awareness (customer awareness of the brand) through digital marketing (digital marketing) and customer loyalty through customer relationship management strategies in the Exist Autodetailing Yogyakarta vehicle body maintenance business.